2004
DOI: 10.1094/fg-2004-1020-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Winter Wheat Forage As Affected by Lime

Abstract: The majority of winter wheat (Triticum aestivum L.) planted in the southern Great Plains is intended for forage or dual‐purpose (grazing and grain) production. Up to 28% of Oklahoma wheat fields have a soil pH less than 5.5 (0‐ to 6‐inch depth) and should be limed to sustain forage and grain wheat yields. This study investigated the effects of seven lime rates on fall forage yields and quality of a winter wheat cultivar planted in a field with the initial pH of 4.5. Soil pH was increased as lime rate increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
4
0
2
Order By: Relevance
“…As for lime rates, from one to three tonnes per hectare, contribution was made to the higher values of the wheat quantitative traits but to a much lesser extent as compared to the variant with 2 tonnes. The results obtained throughout this study are similar with those reached by numerous authors, suggesting a positive effect of the liming on the wheat quantitative traits (Lukin , 2003;Zhang et al, 2004;Brown et al, 2008). However, different lime rates were used because of the different physicochemical properties of soils treated.…”
Section: Resultssupporting
confidence: 89%
“…As for lime rates, from one to three tonnes per hectare, contribution was made to the higher values of the wheat quantitative traits but to a much lesser extent as compared to the variant with 2 tonnes. The results obtained throughout this study are similar with those reached by numerous authors, suggesting a positive effect of the liming on the wheat quantitative traits (Lukin , 2003;Zhang et al, 2004;Brown et al, 2008). However, different lime rates were used because of the different physicochemical properties of soils treated.…”
Section: Resultssupporting
confidence: 89%
“…In 2013, 17.4 million ha of winter wheat were planted in the USA, about 27 % of which were planted in the southern Great Plains including Oklahoma (2.2 million ha) and Texas (2.5 million ha) (USDA National Agricultural Statistics Service). Zhang et al (2004) reported that approximately 70 % of winter wheat fields planted in Oklahoma are used for winter forage production such as grazing, hay or silage, and about 49 % of the wheat fields are managed for dual-purposes (Hossain et al 2004). The considerable amount of forage production in the southern Great Plains could be attributed to the sufficient growing degree-days to produce 120-150 days of wheat pasture for grazing (Holman et al 2010) and it is common practice to graze winter wheat during winter months in the regions (Epplin et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the southern Great Plains, winter wheat has been grown for grain only, forage only, or both forage and grain (Carver et al, 2001;Epplin et al, 2000). Zhang et al (2004) reported that about 70% of winter wheat grown in Oklahoma was managed for winter forage production including grazing or hay production, and Hossain et al (2004) reported that approximately 49% of the winter wheat was managed for dual purposes. Stichler and Livingston (1999) previously stated that a major advantage of winter wheat compared with other small grain species that could be grown for winter forage production is its excellent tolerance to abiotic stresses including cold and drought.…”
mentioning
confidence: 99%